The Role of Blockchain in Documenting Land Users' Rights: The Canonical Case of Farmers in the Vernacular Land Market - Daniel, Desiree; Ifejika Speranza, Chinwe (Frontiers in Blockchain, 2020)
In this article, we discuss the potential of blockchain technology in addressing the documentation of users’ land rights in the informal land rental market. Blockchain technology is a peer-to-peer protocol that can be leveraged to keep track of transactions over the internet. Publicised for its use in the bitcoin revolution, the technology provides transparency and traceability that can be used in the management of land rights. When it comes to the formalisation of land rights, blockchain technology promises to authenticate owners and other users of land, and provides a fixed ledger of land use rights transactions. At present, blockchain technology is being explored as a proof of concept in several countries to track land titles (state to individual). We extend the idea to capture the granting of land use rights (individual to individual) making use of the decentralisation, peer-to-peer nature of blockchain technology. While the technology is not a panacea to all land administration challenges, it can offer an effective means to manage land transactions, provide digital documentation to actors in the informal land rental market and reduce inefficiency in land systems. However, the uptake of the technology in land administration is limited by human related factors. These limitations include, but are not limited to, the accuracy of data being entered into the system, the ability of the system to facilitate data preservation, pre-existing institutional and legal pillars, and the digital divide across communities. Part of overcoming these barriers requires the political will of governments to invest in digital technologies and develop institutional capacities to overcome current limitations to bring land management into the industry 4.0 era.